Cytoplasmic Darkness and PDIA3 Expression as Morphological and Molecular Indicators of Bovine Oocyte Competence for In Vitro Embryo Production: Cytoplasmic Darkness and PDIA3 in Bovine Oocytes - Mehedi, Sohanug; Das, Rajosree; Reza, Tasmi Binta; Jahan, Iffat Nur; Amin, Md Ruhul; Hossain, Md Munir (Research in Agriculture Livestock and Fisheries, 2025)
In vitro embryo production (IVP) is a key biotechnology for accelerating genetic improvement in cattle. Oocyte quality is the primary determinant of IVP success. Among non-invasive selection markers, cytoplasmic coloration-particularly dark-colored cytoplasm (DCC) has been proposed as a visual indicator of lipid content and metabolic competence. This study evaluated the developmental potential of bovine oocytes based on cytoplasmic appearance and validated their competence through PDIA3 gene expression. Cumulus-oocyte complexes (COCs) collected from slaughterhouse ovaries were classified into dark-colored cytoplasm (DCC) and light-colored cytoplasm (LCC) groups and subjected to in vitro maturation (IVM), fertilization (IVF), and culture (IVC). DCC oocytes exhibited significantly greater increases in oocyte diameter (11.60 ± 0.55 µm vs. 4.68 ± 0.31 µm; p = 0.0004) and cumulus expansion (225.8 ± 17.0 µm vs. 142.8 ± 15.1 µm; p < 0.001). Developmental outcomes were also superior in the DCC group, with fertilization (84.53 ± 2.49% vs. 67.80 ± 5.37%; p = 0.015), cleavage (84.53 ± 2.49% vs. 67.80 ± 5.37%; p = 0.017), and blastocyst formation rates (37.39 ± 3.03% vs. 19.41 ± 2.39%; p = 0.0034) significantly higher than in the LCC group. To validate these phenotypic differences, PDIA3 expression was analyzed in germinal vesicle (GV) and metaphase II (MII) oocytes. DCC-derived oocytes showed significantly elevated PDIA3 transcript levels, strengthening the link between cytoplasmic coloration and molecular competence. These findings establish cytoplasmic darkness, is a practical indicator of oocyte quality, and PDIA3 expression validates this morphological assessment at the molecular level. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 149-160